Efektivitas Metode Problem Based Learning dengan Brainstorming dalam Bingkai Bimbingan Kelompok untuk Meningkatkan Pemahaman Materi Pendidikan Pancasila Tingkat Sekolah Dasar - Habsy, Bakhrudin All; Widyastutik, Dwi Rahayu; Nafisah, Candara Aulia; Senja, Agesti Tria Fatma (TSAQOFAH, 2024)
Pancasila education is a basic thing that must be learned in the world of education. Through Pancasila education, students can gain knowledge and basic values of the Indonesian nation. Teachers have an important role in encouraging and providing facilities for students to actively participate in learning activities. The PBL model is an effective method in developing these abilities through independent learning, investigation, and problem solving in small groups under the guidance of the teacher. Researchers used quantitative methods and literature studies in the article we wrote. With the results that can be concluded that at SDN Gununganyar 273, before the teacher establishes the PBL method with brainstorming, students are not maximized in understanding Pancasila education lessons. But after the teacher applied the PBL method, the students' understanding of Pancasila education increased slightly. In applying the PBL method strategy as well as the brainstorming method can help students understand concepts better because it provides opportunities for learners to build their own concepts by finding solutions to the problems given. However, both methods also have advantages and disadvantages, one of the advantages is that students become more active in learning activities, while the disadvantage is that students who are rarely active will be left behind in learning activities.